Identification of Trichosporon asahii in environmental waste (International Journal of Food and Nutritional Sciences, 2023)
The genus Trichosporon's most clinically significant pathogenic yeast is Trichosporon asahii, which can produce both summer-type hypersensitivity pneumonitis and deep-seated infections. Utilising DRBC (dichloran rose bengal chloramphenicol) medium and the polymerase chain reaction (PCR), we were able to separate 29 colonies of T. asahii from environmental materials. According to our research, T. asahii is found throughout nature.